PERAMALAN PRODUKSI AIR BERSIH OLEH PERUSAHAAN DAERAH AIR MINUM BATULANTEH KABUPATEN SUMBAWA MENGGUNAKAN METODE REGRESI - Koko Hermanto; Silvia Firda Utami; Ryan Suarantalla (Program Studi Teknik Industri, Fakultas Rekayasa Sistem, 2020)
Water is one of the natural resources which is a basic human need that cannotseparated every day, therefore good quality water that is suitable for use is needed. CompanyDrinking Water (PDAM) Sumbawa Besar is the only company that supplies clean waterfor the needs of residents of the city of Sumbawa Besar and its surroundings. One of the obstacles for the companyin meeting the need for clean water is the limited debit of the available water supply considering thatThe city of Sumbawa Besar is categorized as a drought area. Therefore it is necessary to planto manage the available water resources. Based on this, the researchers providethe future use of clean water produced by PDAM is usefulbecome material for community planning in using groundwater. In this study, the methodused to determine or predict the use of clean water produced by PDAMBantulante is a regression method, namely the linear regression method, the cudratic regression method or the methodcubic regression. Determination of the best method of the three methods is determined by the value of R squareThe largest, from the analysis using SPSS, it is found that the cubic regression method has an R square valuethe largest compared to the other two methods, where the R square value is 0.572. ForecastingUsing the selected method, the highest water usage was obtained in January, namelyas much as 402,908.60 m3and the lowest was in December, namely 354,747.60 m3. Where is the levelthe accuracy of the forecasting value is 99.99%.